Analisis Layanan Home Care dengan Senam Yoga dalam Menangani Kecemasan pada Ibu Hamil di Kabupaten Bulukumba - Erniawati Erniawati; Ariani Ariani; Husnul Khatimah; Kurniati Akhfar (Lembaga Pengembangan Kinerja Dosen, 2023)
Pregnancy is a period when pregnant women experience physiological and psychological changes. Physical changes that occur during pregnancy can cause complaints or discomfort during pregnancy, which include physical discomfort during pregnancy including back pain, low back pain, difficulty sleeping at night/insomnia, and leg cramps. Meanwhile, psychological discomfort that can occur in pregnant women is anxiety and fear of facing the birth process. Anxiety is one of the psychological changes in the third trimester because it is getting closer to the birth process. Resulting in excessive anxiety during pregnancy can trigger abortion, premature birth, low birth weight, fetal defects, fetal growth retardation, and postpartum depression. Three out of five third trimester pregnant women who were encountered experienced anxiety approaching labor, namely sleep disturbances. Practicing yoga during pregnancy is a useful solution as a self-help medium that will reduce discomfort during pregnancy and help with the birthing process. When pregnancy enters the third trimester, the mother will experience increasingly serious and intense anxiety in dealing with the birth process.